2015
DOI: 10.1016/j.actamat.2015.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Metal/ceramic interface structures and segregation behavior in aluminum-based composites

Abstract: a b s t r a c tTrimodal Al alloy (AA) matrix composites consisting of ultrafine-grained (UFG) and coarse-grained (CG) Al phases and micron-sized B 4 C ceramic reinforcement particles exhibit combinations of strength and ductility that render them useful for potential applications in the aerospace, defense and automotive industries. Tailoring of microstructures with specific mechanical properties requires a detailed understanding of interfacial structures to enable strong interface bonding between ceramic reinf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 70 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…Otherwise, as shown in Figure f and h, both the Mg and O elements are also enriched at the interface between the matrix and glassy particles. The diffusion of Mg at the interface may improve the interfacial wettability and enhancing the interfacial bonding strength …”
Section: Resultsmentioning
confidence: 99%
“…Otherwise, as shown in Figure f and h, both the Mg and O elements are also enriched at the interface between the matrix and glassy particles. The diffusion of Mg at the interface may improve the interfacial wettability and enhancing the interfacial bonding strength …”
Section: Resultsmentioning
confidence: 99%
“…Previous studies on cryomilled‐plus‐consolidated bulk B 4 C‐reinforced Al–Mg alloy (Al 5083) matrix nanocomposites demonstrated that Mg segregates to the B 4 C/Al interface and forms Mg‐rich layers near the interface, as shown in Figure . A B 4 C particle located in the center of Figure a is in contact with both a coarse grained Al region at Interface 1 and ultrafine grained Al regions at Interfaces 2–4.…”
Section: Introductionmentioning
confidence: 90%
“…A variety of severe plastic deformation techniques are available to achieve grain refinement in materials, including equal channel angular pressing (ECAP), high pressure torsion (HPT), cryorolling, and ball milling . Compared to cryorolling and ECAP, which apply mechanical deformation to bulk materials to refine the grain structure, cryomilling is a powder metallurgy technique that generates nanocrystalline powder via severe plastic deformation .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increase in strength of the material is limited to the modulus and volume fraction of stronger reinforcement . Such an approach of material design leads to stronger material, with reduced ductility due to poor interface between reinforcement and matrix . Beyond this conventional wisdom, nature has also shown examples of composite materials (e.g., intervertebral disc, etc.)…”
Section: Comparison Of Experimental and Theoretical Values For Effectmentioning
confidence: 99%